1983
DOI: 10.1002/cber.19831160327
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazabole: Elektrophile Substitutionen und Röntgenstrukturuntersuchungen

Abstract: Elektrophil induzierte Substitutionsreaktionen an den Boratomen der Pyrazabole [R2BpzI2 mit "BBr, erfolgen ohne Austausch von Boratomen. Alle vier Substituenten R werden gegen Br substituiert (Ausnahme R = C,H,), wobei "B-NMR-spektroskopisch verschieden substituierte Pyrazabole als Zwischenprodukte nachgewiesen und in einigen Fallen isoliert wurden. Dabei weisen die NMR-Daten der Umsetzung von [(CzH5)2Bpz]z mit BBr, auf eine ionische Zwischenstufe fur diese Austauschreaktion hin. Eine schrittweise Substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…In general, pyrazaboles with symmetrical 4,8-disubstitutions at the boron atom have been synthesized by the reaction of amine complexes of borane or organoborane reagents with pyrazole under reflux conditions in toluene [27,28]. The other synthetic route employed is by functionalizing the hydrogen coordinated to boron of pyrazabole by other groups [42,43]. In the case of gem boron disubstituted or asymmetrically boron monosubstituted materials, the synthesis is challenging due to unpredictable reaction of the bis(pyrazolyl)borate salt with the amine complexes of the boranes bearing good leaving group [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…In general, pyrazaboles with symmetrical 4,8-disubstitutions at the boron atom have been synthesized by the reaction of amine complexes of borane or organoborane reagents with pyrazole under reflux conditions in toluene [27,28]. The other synthetic route employed is by functionalizing the hydrogen coordinated to boron of pyrazabole by other groups [42,43]. In the case of gem boron disubstituted or asymmetrically boron monosubstituted materials, the synthesis is challenging due to unpredictable reaction of the bis(pyrazolyl)borate salt with the amine complexes of the boranes bearing good leaving group [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental BCl bond length in seven molecules with the CSD Refcode: CAQNEN, FUMXAO, ACNBCL, TUWMEF, BUGGUF, ADAJIA, and ADAJEW is between 1.793 and 1.917Å (see Tables and ).…”
Section: Resultsmentioning
confidence: 99%
“…The parent pyrazabole, {H 2 B(-pz)} 2 has been known since 1966 when it was reported by Trofimenko contemporaneously with the discovery of Tp ligands (Trofimenko, 1966). Since then, numerous substituted pyrazaboles have been prepared and structurally investigated (Alcock & Sawyer, 1974;Cavero et al, 2008;Niedenzu & Niedenzu, 1984;Niedenzu & Nö th, 1983;Trofimenko, 1966). In a number of recent studies, it has been demonstrated that certain substituted pyrazaboles possess unique photophysical and electrochemical properties and could thus find promising applications in organic photovoltaics (OPVs) and non-linear optics (Jadhav et al, 2013(Jadhav et al, , 2015Misra et al, 2013Misra et al, , 2014Patil et al, 2017).…”
Section: Figurementioning
confidence: 99%
“…For the chemistry of divalent lanthanide scorpionate complexes, see: Davies et al (1985) For general information on the chemistry and structures of pyrazaboles, see: Cavero et al (2008), Niedenzu & Niedenzu (1984), Niedenzu & Nö th (1983), Trofimenko (1966).…”
Section: Figurementioning
confidence: 99%